Penerapan Model Pembelajaran Group Investigation Melalui Pendekatan Saintifik Untuk Meningkatkan Kemampuan Penalaran Matematis dan Resiliensi Matematis Siswa - Dian Karina; Enny Putri Cahyani (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research aims to examine whether the improvement in students' mathematical reasoning abilities who use the Group Investigation learning model is better than the abilities of students who use the Group Investigation learning model. Apart from that, it also reveals the students' attitudes towards the Group Investigation learning model. The method in this research is experimental and research design using pretest and posttest in experimental and control classes. The population in this study were all students in class X OTKP SMKN 1 Cipanas, Cianjur Regency. Samples were taken at random from class, namely from six classes, two classes totaling 32 students were obtained, where class X OTKP 1 was the experimental class and class X OTKP 2 was the control class. The experimental class uses the Group Investigation learning model, while the control class uses conventional learning. Research data was obtained through instruments in the form of pretest and posttest mathematical reasoning abilities, student attitude scales, and observation sheets. Pretest data was processed through a normality test, homogeneity test, and equality of two means test, while posttest data was processed through a normality test, homogeneity test, and difference of two means test using SPSS 16 software. The results showed that the mathematical reasoning abilities of students who used the Group learning model Investigation is better than the ability of students who use conventional learning. Students show an attitude of confidence, self-confidence, actively involve themselves in discussions and are persistent in the Group Investigation learning model.